Aneurysms of the aorta and peripheral arteries - Synowiec, Tomasz; Chęciński, Paweł; Micker, Maciej (Przewodnik Lekarza/Guide for GPs, 2006)
Aneurysms are segmental dilatations of the artery wall that cause the vessel to be larger than 1.5 times its normal diameter. It is quite often diagnosis, especially in older patients. Most of the artery dilatation is asymptomatic. These can continue to expand and rupture spontaneously which is connected with a high risk of death. The most common localization of aneurysms is the abdominal aorta but the pathology also affects other arteries. There are two effective methods of treatment: open surgery and endovascular techniques, which prevent aneurysm from expand and rupture. The knowledge of this disease is essential in the process of successful treatment.